EXPLORATION OF PROBLEM-SOLVING ABILITIES OF PROSPECTIVE PHYSICS TEACHERS BASED ON MULTIPLE INTELLIGENCES IN FLUID MECHANICS - Wahyuni, Andi Sri Astika; Usman, Usman; Setiawan, Trisno (Universitas Negeri Makassar, 2025)
This study aims to explore the problem-solving abilities of prospective physics teachers based on multiple intelligences in the context of fluid mechanics. The research employed a survey approach by combining a problem-solving test and a multiple intelligences questionnaire to identify students’ dominant intelligence profiles. The participants were categorized into three dominant intelligence types: verbal-linguistic, logical-mathematical, and spatial. The results indicate notable differences in problem-solving characteristics among the groups. Students with verbal-linguistic intelligence tended to demonstrate higher proficiency in understanding and articulating concepts through coherent and argumentative explanations, resulting in more comprehensive verbal solutions. Students with logical-mathematical intelligence solved problems by identifying patterns and physical quantities using systematic mathematical procedures, although their solutions often lacked detailed conceptual explanations. Meanwhile, students with spatial intelligence primarily used visualization, including sketches, diagrams, or other representations, to interpret situations and derive solutions. These findings suggest that multiple intelligences influence students’ cognitive strategies for solving physics problems. The study highlights the need for instructional designs that are responsive to students’ diverse intelligence profiles to optimize the development of problem- solving skills.